Hizikia fusiforme functional oil (HFFO) prevents neuroinflammation and memory deficits evoked by lipopolysaccharide/aluminum trichloride in zebrafish - Nie, Ying-Ying; Zhou, Long-Jian; Li, Yan-Mei; Yang, Wen-Cong; Liu, Ya-Yue; Yang, Zhi-You; Ma, Xiao-Xiang; Zhang, Yong-Ping; Hong, Peng-Zhi; Zhang, Yi (Frontiers in Aging Neuroscience, 2022)
Background Oxidative stress, cholinergic deficiency, and neuroinflammation are hallmarks of most neurodegenerative disorders (NDs). Lipids play an important role in brain development and proper functioning. Marine-derived lipids have shown good memory-improving potentials, especially those from fish and microalgae. The cultivated macroalga Hizikia fusiforme is healthy food and shows benefits to memory, but the study is rare on the brain healthy value of its oil. Previously, we had reported that the Hizikia fusiforme functional oil (HFFO) contains arachidonic acid, 11,14,17-eicosatrienoic acid, phytol, and other molecules displaying in vitro acetylcholinesterase inhibitory and nitroxide scavenging activity; however, the in vivo effect remains unclear. In this study, we further investigated its potential effects against lipopolysaccharides (LPS)- or aluminum trichloride (AlCl3)-induced memory deficiency in zebrafish and its drug-related properties in silica. Methods We established memory deficit models in zebrafish by intraperitoneal (i.p.) injection of lipopolysaccharides (LPS) (75 ng) or aluminum trichloride (AlCl3) (21 μg), and assessed their behaviors in the T-maze test. The interleukin-1β (IL-1β), tumor necrosis factor-α (TNF-α), acetylcholine (ACh), and malondialdehyde (MDA) levels were measured 24 h after the LPS/AlCl3 injection as markers of inflammation, cholinergic activity, and oxidative stress. Furthermore, the interaction of two main components, 11,14,17-eicosatrienoic acid and phytol, was investigated by molecular docking, with the important anti-inflammatory targets nuclear factor kappa B (NF-κB) and cyclooxygenase 2 (COX-2). Specifically, the absorption, distribution, metabolism, excretion, and toxicity (ADMET) and drug-likeness properties of HFFO were studied by ADMETlab. Results The results showed that HFFO reduced cognitive deficits in zebrafish T-maze induced by LPS/AlCl3. While the LPS/AlCl3 treatment increased MDA content, lowered ACh levels in the zebrafish brain, and elevated levels of central and peripheral proinflammatory cytokines, these effects were reversed by 100 mg/kg HFFO except for MDA. Moreover, 11,14,17-eicosatrienoic acid and phytol showed a good affinity with NF-κB, COX-2, and HFFO exhibited acceptable drug-likeness and ADMET profiles in general. Conclusion Collectively, this study's findings suggest HFFO as a potent neuroprotectant, potentially valuable for the prevention of memory impairment caused by cholinergic deficiency and neuroinflammation.